Agrofloresta e reforma agrária: o caso do assentamento Mario Lago em Ribeirão Preto - SP - Gomes, Olívia Desuó [UNESP] (2015)
A territory, as a category of geographical analysis, is defined by the power relations present on it. Historically at the Brazilian agricultural framework, those relations have resulted on land concentration, expropriation of rural workers and environmental degradation. So it is at the surroundings of the city of Ribeirão Preto - SP (Brazil), where the sugarcane industry hold most part of the available land and uses it for agribusiness. Thus, the present study aimed at analyzing the territorial transformations that occurred at the Mario Lago Agrarian Reform Settlement with regard to the Agroforestry Project that is being implemented, a model that runs against the present agro-industrial logics, as it has in essence the union between agriculture, man and forest. From the analysis made, it was revealed that adopting Agroforest Systems lead to the resumption of the autonomy of small farmers and to the increase of their appreciation for their work, combining food production and environmental preservation. It was concluded that the application of Agroforestry models by members of the Brazilian Landless Workers Movement (MST) is a feasible way for consolidating Agroecology practices in this country, comprising a power struggle and resistance against the Brazilian agrarian hegemony